2011
DOI: 10.1016/j.mib.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Enteric pathogen exploitation of the microbiota-generated nutrient environment of the gut

Abstract: Residing within the intestine is a large community of commensal organisms collectively termed the microbiota. This community generates a complex nutrient environment by breaking down indigestible food products into metabolites that are used by both the host and the microbiota. Both the invading intestinal pathogen and the microbiota compete for these metabolites, which can shape both the composition of the flora, as well as susceptibility to infection. After infection is established, pathogen mediated inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 56 publications
1
67
0
Order By: Relevance
“…Although it is possible that C. difficile directly impairs expansion of other microbial groups by suppression or competition for ecological niches, it is also possible that C. difficile infection indirectly modulates intestinal microbiota composition by augmenting mucosal inflammation. Indeed, intestinal inflammation induced by enteric pathogens has been shown to affect colonic bacteria density (28), suppress populations of indigenous intestinal bacteria (20), and otherwise alter microbiota composition in ways that favor colonization and expansion of exogenous microbial populations (28), including pathogenic bacteria (35). Our results indicate C. difficile infection induces intestinal inflammation that persists for at least 30 days.…”
Section: Discussionmentioning
confidence: 64%
“…Although it is possible that C. difficile directly impairs expansion of other microbial groups by suppression or competition for ecological niches, it is also possible that C. difficile infection indirectly modulates intestinal microbiota composition by augmenting mucosal inflammation. Indeed, intestinal inflammation induced by enteric pathogens has been shown to affect colonic bacteria density (28), suppress populations of indigenous intestinal bacteria (20), and otherwise alter microbiota composition in ways that favor colonization and expansion of exogenous microbial populations (28), including pathogenic bacteria (35). Our results indicate C. difficile infection induces intestinal inflammation that persists for at least 30 days.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, according to the metabolites present in the small intestine and in the colon, toxin genes might be differentially expressed in the gut. Accordingly, formate and acetate (directly obtained from pyruvate) predominate in the small intestine, while the levels of propionate and butyrate are higher in the colon (84). Such a control has been described in Salmonella enterica serovar Typhimurium: formate acts as a diffusible signal to induce the expression of invasion genes in the small intestine, the site that is preferentially colonized by this enteropathogen, while butyrate is present at higher concentrations in the colon and represses these genes (85,86).…”
Section: Figmentioning
confidence: 95%
“…They produce substances including vitamins, volatile or short-chain fatty acids (SCFAs) and polyamines which are absorbed throughout the intestinal wall and used directly by intestinal epithelial cells or other cells of the body [170,171]. SCFA profoundly influence gut barrier functions, host immunity, epithelial proliferation and bacterial pathogenesis [172]. Zheng et al [171] showed extensive gut microbiota modulation of host systemic metabolism involving shortchain fatty acids, tryptophan and tyrosine metabolism, and possibly a compensatory mechanism of indole-melatonin production.…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Beneficial and pathogen microorganism compete with each other for the attachment sites and for nutrients, so microbiota and their products can prevent pathogen colonization directly. On the other hand, microbiota acts on barrier functions also indirectly by stimulating mucosal immune system [172]. The abundant antigenic stimulus supplied by microbiota and their products are essential for the stimulation of immune system cells locally and systemically [173][174][175].…”
Section: Intestinal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation